Buddhist Councils (Sangiti) and its Literature: A Review - Potbhare, *Balaji Mahadev; Vanmala, Wakode (International Journal of Ayurveda and Pharma Research, 2019)
There are two main philosophical sciences in India; atheistic (Charavka, Jain and Bauddha) and theist (Sankhya, Yoga, Nyaya, Vaishehika, Purva mimansa and Uttar mimansa). In India, abundant literatures of philosophical sciences are available except Buddhist literature and the reasons are unknown. Buddhist literatures were in Pali language which was a dialect of ancient India and to preserve the invaluable teaching of the Buddha, till dated six Councils (Shangiti) were convened out of which three councils were assembled in ancient India. It is said that the knowledge of history of Indian culture is incomplete without the knowledge of Pali literature. Ayurveda is a Darshanshashtra (Philosophy) as well as clinical science having the goal of Moksha. Every Darshanshashtra has its goal to achieve the Moksha. Aastika and Nastika darshanshashtras have their influence on Ayurveda. The purpose of this paper is to know about the Buddhist councils along with at least appellations of the Buddhist literature.